Chitosan hydrogel vaccine generates protective CD8 T cell memory against mouse melanoma. Issue 7 (24th February 2015) - Highton, Andrew J; Kojarunchitt, Thunjiradasiree; Girardin, Adam; Hook, Sarah; Kemp, Roslyn A
Abstract : CD8 + T cells are important in the control of viral infections and cancers because of their cytolytic activity. A vaccine able to generate these cells could be beneficial in the prevention or treatment of these diseases. Chitosan hydrogel is a promising vaccine formulation that has previously been shown to generate effector CD8 + T cells in a mouse model. This vaccine promotes sustained release of antigen and adjuvant, which generates a robust effector response. For longer lasting immunity, a memory population of these CD8 + T cells is required to control further disease. We found that vaccination with chitosan hydrogel or dendritic cells using ovalbumin protein as a model antigen and Quil‐A adjuvant provided protection in a subcutaneous melanoma challenge 30 days later. Ovalbumin‐specific memory CD8 + T cells were detectable following vaccination with the chitosan hydrogel but not the dendritic cell vaccine and an in vivo cytotoxicity assay demonstrated specific lysis of target cells in chitosan hydrogel vaccinated mice but not those receiving dendritic cell vaccination. These results demonstrate that vaccination with chitosan hydrogel is equally effective as dendritic cell vaccination in tumour protection but has more readily detectable immune correlates of protection. This may be advantageous in predetermining protection in vaccinated individuals.